PENGARUH SELF-LEADERSHIP TERHADAP ENTREPRENEURIAL PERFORMANCE DENGAN SELF-EFFICACY SEBAGAI VARIABEL MEDIASI DI PROJECT BUSINESS MAHASISWA IBM 2018 - Michael Helton Rubowo; Christina Sudyasjayanti (Universitas Ciputra Surabaya, 2022)
The study aims to find out the influence of self-leadership on entrepreneurial performance with self-efficacy mediating this relationship in the 2018 IBM student project business at Ciputra University Surabaya. Leaders have an important role, so the CEO was used as a criterion in selecting the population. The population in this study was the CEO of the 2018 IBM student project business at Ciputra University Surabaya. To answer the problems in this study, the authors uses Structural Equation Modeling (SEM) measuring instrument using PLS. The sampling technique was conducted using probability sampling techniques using the Slovin to determine the number of samples. Collecting data by distributing questionnaires using a Likert scale. The results of this study indicate that 1) self-leadership has a positive and significant effect on entrepreneurial performance 2) self-leadership has a positive and significant effect on self-efficacy 3) self-efficacy has a positive and significant effect on entrepreneurial performance 4) self-efficacy mediates the relationship of self -leadership and entrepreneurial performance partially. Key words : self-leadership, self-efficacy, entrepreneurial performance, CEO of project business